Application of Active Packaging in Refrigerated Rainbow Trout (Oncorhynchus mykiss) Fillets Treated with UV-C Radiation - Maria Lúcia G. Monteiro (Applied Sciences, 2020)
This study investigated the effects of oxygen-scavenger packaging and UV-C radiation at two doses, alone or in combination, on lipid oxidation (malondialdehyde levels), protein oxidation (carbonyl content), instrumental color and texture parameters in rainbow trout fillets stored at 4 ± 1 °C for 9 days. The treatments were AP (air packaging), OSP (oxygen-scavenger packaging), AUV1 (air packaging + UV-C at 0.102 J/cm2), OSUV1 (oxygen-scavenger packaging + UV-C at 0.102 J/cm2), AUV3 (air packaging + UV-C at 0.301 J/cm2), and OSUV3 (oxygen-scavenger packaging + UV-C at 0.301 J/cm2). Lipid oxidation, protein oxidation, lightness and yellowness increased, while redness, hardness and chewiness decreased during storage in all treatments (p < 0.05). OSP, OSUV1 and OSUV3 exhibited lower yellowness, total color difference (ΔE), lipid and protein oxidation, and higher redness, hardness and chewiness than air packaging (AP; p < 0.05), being similar to each other concerning these parameters throughout storage (p > 0.05). AUV3 showed higher lipid oxidation, protein oxidation, yellowness, ΔE, and lower redness, hardness and chewiness followed by AUV1 than AP (p < 0.05). UV-C at these doses was not adequate for refrigerated trout fillets by inducing oxidative degradation. O2 scavenger was effective in preventing the adverse effects from storage period and UV-C, independently of the dose, and could be a simple and powerful alternative to make feasible the industrial application of UV-C at 0.102 and 0.301 J/cm2 in refrigerated rainbow trout fillets, which has proven antimicrobial effect and it is a promising non-thermal technology for the fish production chain.